Multistate resistive switching characteristics of ZnO nanoparticles embedded polyvinylphenol device - Jung, Jihee; Kwon, Dahye; Jung, Hunsang; Lee, Kyungmin; Yoon, Tae-Sik; Kang, Chi Jung; Lee, Hyun Ho (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] Multistate resistive switching device was demonstrated with organic/inorganic nanocomposite layer of polyvinylphenol (PVP) embedded with zinc oxide nanoparticles (ZnO NPs). Both cap (ITO/ZnO NPs+PVP/Al) and crossbar (Pt/ZnO NPs+PVP/Al) device formats were examined, respectively. Extending range of voltage sweep could show adaptive memory effect, which could roughly emulate analog resistive switching device. In addition, potentiation and depression behaviors were also examined with 50 time consecutive pulsed bias (+2.0V and −2.0V respectively) having 10ms width measured at read voltage of −0.2V. A new possibility of analog resistive switching can be further pursued with the ZnO NPs+PVP nanocomposite.